Medium-Dose Chronic Cannabidiol Treatment Reverses Object Recognition Memory Deficits of APPSwe/PS1ΔE9 Transgenic Female Mice - Coles, Madilyn; Watt, Georgia; Kreilaus, Fabian; Karl, Tim (Frontiers in Pharmacology, 2020)
Alzheimer’s disease (AD) is a neurodegenerative disease that causes behavioural and cognitive impairments. The phytocannabinoid cannabidiol (CBD) has anti-inflammatory, anti-oxidant and neuroprotective properties and in vitro and limited in vivo evidence suggests that CBD possesses therapeutic-like properties for the treatment of AD. Cannabinoids are known to have dose-dependent effects and the therapeutic potential of medium dose CBD for AD transgenic mice has not been assessed in great detail yet. 12-month-old control and APPSwe/PS1ΔE9 (APPxPS1) transgenic female mice were treated daily via intraperitoneal injection with 5 mg/kg bodyweight CBD (or vehicle) commencing three weeks prior to the assessment of behavioural domains including anxiety, exploration and locomotion, motor functions, cognition, and sensorimotor gating. APPxPS1 mice exhibited a hyper-locomotive and anxiogenic-like phenotype and had wild type-like motor and spatial learning abilities, although AD transgenic mice took generally longer to complete the cheeseboard training (due to a lower locomotion speed). All mice displayed intact spatial memory and retrieval memory, but APPxPS1 mice showed reduced levels of perseverance in the cheeseboard probe trial. Importantly, vehicle-treated APPxPS1 mice were characterised by object recognition deficits and delayed spatial learning, which were reversed by CBD treatment. Finally, impairments in sensorimotor gating of APPxPS1 mice were not affected by CBD. In conclusion, medium dose CBD appears to have therapeutic value for the treatment of particular behavioural impairments present in AD patients. Future research should consider the molecular mechanisms behind CBD’s beneficial properties for AD transgenic mice.